Analysis of Muslim-Friendly Tourism Potential in Padang Ganting Hot Spring Tourism, Tanah Datar District, West Sumatra, Indonesia - Siska Mandalia; Harry Yulianda; Habibullah Adriz (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This study aims to analyze the potential of Muslim-friendly tourism and the obstacles to its implementation at the Padang Ganting hot spring tourist destination in Tanah Datar Regency West Sumatera Indonesia. The focus of the research is to identify the four components of Muslim-friendly tourism destinations with the standardization issued by Indonesia Muslim Travel Index (IMTI). They are Accessibility (access), Communication (communication), Environment (environment), and Service (service) Methods: Data were collected by using observation, in-depth interviews and document studies. Furthermore, the data that has been collected will be analyzed using descriptive qualitative analysis techniques. Result: The results show that the potential of Muslim-friendly tourism in the Padang Ganting hot spring is quite large, although there are still obstacles with the following indications: 1) potential Access, that is the road has been paved but is still narrow for four-wheeled vehicles or buses to pass, parking lots and roads exit still needs improvement. 2) The communication aspect includes Muslim-friendly information services through posters and stakeholder training by the district government of Tanah Datar regency, however, is still not geared towards Muslim-friendly tourism and no digital marketing has been carried out. 3) Environmental aspects have supported Muslim tourists but Wi-Fi service is not yet available. 4) There are services and facilities for Muslim tourists but there is no halal food certification, Ramadan services and the need to improve environmental hygiene. Benefits/Contributions: This research is expected to add to knowledge, especially in the analysis of Muslim-friendly tourism potential in a tourist destination. Contribution: This research can contribute to knowledge, particularly with regard to examining the potential for Muslim-friendly tourism in a tourist destination.